Intranasal immunization with a single dose of the fusion protein formulated with a combination adjuvant induces long-term protective immunity against respiratory syncytial virus - R. Garg; L. Latimer; V. Gerdts; A. Potter; S. van Drunen Littel-van den Hurk (Human Vaccines & Immunotherapeutics, 2017)
Respiratory syncytial virus (RSV) is the most common cause of respiratory tract infections in both children and elderly people. In this study we evaluated the short- and long-term protective efficacy of a single intranasal (IN) immunization with a RSV vaccine formulation consisting of a codon-optimized fusion (F) protein formulated with poly(I:C), an innate defense regulator peptide and a polyphosphazene (ΔF/TriAdj). This vaccine induced strong systemic and local immune responses, including RSV F-specific IgG1 and IgG2a, SIgA and virus neutralizing antibodies in mice. Furthermore, ΔF/TriAdj promoted production of IFN-γ-secreting T cells and RSV F85–93-specific CD8+ effector T cells. After RSV challenge, no virus was recovered from the lungs of the vaccinated mice. To evaluate the duration of immunity induced by a single IN vaccination, mice were again immunized once with ΔF/TriAdj and challenged with RSV five months later. High levels of IgG1, IgG2a and virus neutralizing antibodies were detected in the ΔF/TriAdj-vaccinated animals. Moreover, this vaccine formulation induced robust local SIgA production and IgA-secreting memory B cell development, and conferred complete protection against subsequent RSV challenge. In conclusion, a single IN vaccination with RSV ΔF protein formulated with TriAdj induced robust, long-term protective immune responses against RSV infection.